Physical Behaviour of Thermally Affected Bronze and Brass - Kaiser, Samiul; Kaiser, Mohammad Salim (Universitas Negeri Malang, 2020)
The physical behavior of thermally affected cast copper, aluminium bronze and brass has been studied by subjecting to heating isochronally for one hour at a range of 600°C. It shows that solid-solution hardening takes place into the Al added bronze and Zn added brass metal. Due to heating Al forms hard and brittle intermetallic of copper aluminites into bronze metal which responses some age hardening effects. The electrical conductivity of the metals increases initially through heat treatment due to stress relieving and finally decreases due to formation of intermetallic precipitates. The color of the heated samples are also studied through tristimulus color ‘L*’, ‘a*’ and ‘b*’ values which were analyzed and evaluated in MATLAB software. It is found that incorporation of Al and Zn affects the colour of cast Cu. The overall change of color occurs with increasing heating temperature due to chemical changes like oxidization, intermetallic formation, dissolution of phases, precipitation coarsening and recrsystallization. Due to change of hardness and microstructural properties of the experimental metals the sound intensity level also decreases at high heating temperature. A microstructural study confirms that the cast alloys contents the different phases of grains and bring about re-crystallized state after heating at 500°C for one hour.